Design in Partnership and Projects with High Social Impact an experience with games as catalysts for a university extension project - Léste, João V.; Sousa, Lucas B.; Farbiarz, Jackeline L.; Dias, Cynthia M.; Farbiarz, Alexandre (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
The design in Partnership method has many intersections with Youth Participatory Action research (YPAR) methodologies. This document will explore their application to propose conducting projects with high social impact, potentiating youths to take on leading roles in their communities, using as a reference a project based on Tabletop Games to promote the integration of underprivileged youths in academic spaces. These methods are also very in line with more modern approaches to university extension projects, which focus on the relationship between universities and the communities surrounding them, with the intent of promoting social change through education and liberation.